2020
DOI: 10.1002/biof.1612
|View full text |Cite
|
Sign up to set email alerts
|

The role of KLF14 in multiple disease processes

Abstract: Kruppel‐like factor 14 (KLF14) is a newly identified member of the KLF family. Expression of KLF14 is induced by TGF‐β in intrauterine and ectodermal tissue. Initial researches on KLF14 focused on its role in lipid and glucose metabolism. In recent years, however, the role of KLF14 in regulating cell signaling pathways, cell proliferation and differentiation has been explored. Moreover, the research has gradually extended into the field of tumorigenesis and immune regulation. This paper aims to briefly review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 57 publications
(133 reference statements)
0
41
0
Order By: Relevance
“…Moreover, KLF14 is a maternally expressed gene and has a large CpG island across most regions of the open reading frame (ORF). This CG-rich region regulates downstream gene expression and nuclear protein transcription by interacting with coactivators or immune complexes [ 10 ]. Previous studies have shown that KLF14 significantly regulates lipid metabolism and blood glucose levels, which are closely related to the pathogenesis of atherosclerosis, type 2 diabetes, insulin resistance, and other diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, KLF14 is a maternally expressed gene and has a large CpG island across most regions of the open reading frame (ORF). This CG-rich region regulates downstream gene expression and nuclear protein transcription by interacting with coactivators or immune complexes [ 10 ]. Previous studies have shown that KLF14 significantly regulates lipid metabolism and blood glucose levels, which are closely related to the pathogenesis of atherosclerosis, type 2 diabetes, insulin resistance, and other diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…KLF14 is associated with insulin resistance, dyslipidaemia, type 2 diabetes and a female-specific shift of body fat from gynoid to abdominal stores, in agreement with the hip-specific association in women found in our study. In mice, adipocyte-specific deletion of Klf14 results in similar metabolic effects, while Klf14 knockout results in spontaneous tumorigenesis 30 . TBX15 belongs to a family of transcription factors regulating differentiation, proliferation, tissue integrity and epithelial-mesenchymal transition, which are relevant to cancer development and metastasis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells were first cultured in deoxygenated glucose-free DMEM medium using a hypoxic vessel maintained at 37°C for 4 h (95% N 2 and 5% CO 2 ). Then, the cells were transferred onto high glucose DMEM medium containing 10% FBS and cultured under normoxic conditions (5% CO 2 ) at 37°C for 24 h as previously described [ 33 ].…”
Section: Methodsmentioning
confidence: 99%